Human Rights as a Limit to the Prison System in Colombia - Palacios-Guastar, Gloria Cecilia (Universidad Pedagógica y Tecnológica de Colombia, 2016)
lyzing prison system in general, as a subject of Penal and Criminological Sciences, there is a constant discussion based on human rights, as a theoretical and practical structuring of the ideal of a prison system approach. Thus, speaking of a system focused on punishment for a certain behavior, it is necessary to take into account the current conclusion of the doctrinal and normative evolution of human rights in this regard, which above all, provides a limit universal and deontologically applicable to all sanction requiring adetention, but that for our approach it observes carefully the case of Colombia, as the special conditions of vulnerability of rights prevailing in almost all prisons in the country are well known.